Performance Analysis of Regional Revenue and Capital Expenditures in Batam City Government: A Study of the 2018-2022 Period - Yusmita, Neni; Sari, Suci Indah Permata; Aisyah, Rifdah; Yulsiati, Henny (Journal of Regional Economics Indonesia, 2024)
This study aims to analyze the financial performance of the Batam City Government during the 2018–2022 period. The research utilizes secondary data obtained from the Supreme Audit Agency (Badan Pemeriksa Keuangan, BPK), the institution authorized to audit state finances in Indonesia. The analysis methods employed include trend analysis, variance analysis, fiscal decentralization ratio, growth ratio, effectiveness ratio, expenditure management ratio, and capital expenditure ratio. The results indicate that the financial performance of the Batam City Government is generally satisfactory. The trend analysis reveals fluctuations, while variance analysis indicates favorable outcomes in capital expenditure but unfavorable outcomes in locally generated revenue (PAD), as its realization has not met the target. The effectiveness ratio shows that the government is less effective in achieving targeted PAD. Although the growth ratio indicates suboptimal performance, it shows positive growth trends. The capital expenditure ratio demonstrates an ideal proportional allocation. In conclusion, while the financial performance of the Batam City Government over the five years (2018–2022) is relatively strong, annual fluctuations remain a challenge.